Effects of aging on the thermo‐mechanical response of a die casting alloy. Issue 1 (17th December 2018) - Martinez Page, Maria Angeles; Hartmann, Stefan
Abstract: Zamak alloys can be found in a wide variety of components of the automotive, building, electronic, and toy industry. They are preferred to other materials for die casting foundry due to their several advantages. For example, they exhibit a low melting point which allows an economic manufacturing process, they allow the production of components with tight tolerances and are characterized by good mechanical properties. Nonetheless, these alloys show a change in their mechanical behavior over time. This phenomenon is known as aging and it is associated to microstructural transformations such as diffusion and precipitation of alloying elements and phase transformations. In this work, the influence of natural aging on the thermo‐mechanical response is investigated with the help of tension, compression and torsion experiments and a model with aging as an internal variable is proposed.